ALAN'S SCHIZOPHRENIA IN PETER SHAFFER'S EQUUS - Risma Septia Wardani; Anik Cahyaning Rahayu (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
This article is about Alan's schizophrenia in Peter Shaffer's play Equus. Schizophrenia is a kind of mental disorder. The symptoms of Alan's schizophrenia as well as its causes are analyzed and it is related to theory of Freud's psychoanalysis. The research method is descriptive qualitative research method. By using descriptive qualitative research method, the data are processed qualitatively and explained descriptively to answer the research problem statements. The answer of the first problem statement is about the symptoms of Alan's schizophrenia and its causes exposed in the play. The symptoms are delusion and hallucination. Dr. Dysart, as a psychiatrist tries to find out why Alan always adores horse, and he is surprised when one night he blinds six horses with a spike when he has a date with a girl named Jill. He shows some symptoms of schizophrenia like delusion and hallucination through his actions and misinterpretation of a horse. Dysart uses some methods during the treatment to help him cover the things such as hypnosis and give drugs. The answer of the second problem statement shows how Alan's schizophrenia is seen from Freud's psychoanalysis theory Alan' actions and behaviors show that they are influenced by id, ego, and superego.